erythro-2-Morpholino-1,2-diphenylethanol - Karadayi, N; Kazak, C; Öztürk, S; Aydin, M; Arsu, N; Fun, HK; Büyükgüngör, O (INT UNION CRYSTALLOGRAPHY, 2002)
The title compound, C18H21NO2, consists of two aromatic rings and a morpholine ring attached to an ethanol moiety. The molecule is non-planar. There is an intramolecular O-H...N hydrogen bond.
Keywords: Crystallography